Sustainable Pest Management with Hollow Mesoporous Silica Nanoparticles Loaded with β-Cypermethrin - Min Li; Linmiao Xue; Teng Gao; Zhuo Zhang; Dan Zhao; Xing Li; Zhanhai Kang (Agronomy)
β-cypermethrin (BCP) is a broad-spectrum insecticide known for its rapid efficacy. However, it is highly toxic to non-target organisms such as bees and fish, and its effectiveness is limited by a short duration of action. Improving the release profile of BCP is essential for reducing its environmental toxicity while preserving its effectiveness. In this study, hollow mesoporous silica nanoparticles (HMSNs) were synthesized using a self-templating method, and BCP-loaded HMSNs were prepared through physical adsorption. The structural and physicochemical properties of the nanoparticles were characterized using scanning electron microscopy (SEM), transmission electron microscopy (TEM), nitrogen adsorption–desorption analysis, Fourier transform infrared (FT-IR) spectroscopy, dynamic light scattering (DLS), and thermogravimetric analysis (TGA). The BCP release profile was assessed using the dialysis bag method. The results showed that the synthesized nanoparticles exhibited uniform morphology, thin shells, and large internal cavities. The HMSNs had a pore size of 3.09 nm, a specific surface area of 1318 m2·g−1, a pore volume of 1.52 cm3·g−1, and an average particle size of 183 nm. TEM, FT-IR, and TGA analyses confirmed the successful incorporation of BCP into the HMSNs, achieving a drug loading efficiency of 32.53%. The BCP-loaded nanoparticles exhibited sustained-release properties, with an initial burst followed by gradual release, extending efficacy for 30 days. Safety evaluations revealed minimal toxicity to maize seedlings, confirming the biocompatibility of the nanoparticles. These findings indicate that BCP-loaded HMSNs can enhance the efficacy of BCP while reducing its environmental toxicity, providing a biocompatible and environmentally friendly solution for pest control.